The effects of monetary policy on the residential financing for the year 2000-2005 / Aimi Nazihah Azmi - Azmi, Aimi Nazihah (2007)
Several studies show that monetary policy can influence bank to raises the quantity of bank loans available. It also reflected to residential market. The purpose of this study was to know whether the effects of monetary policy in terms of money supply (Ml), interest rate (base lending rate) or import of construction materials and mineral products can influence housing loan. Housing loan here refer to the loans granted to individuals for the purchase of residential property. Monetary policy was generally referred to as either being an expansionary policy (increases in total supply of money in the economy and it was usually used to combat unemployment in a recession by lowering the interest rate) or contractionary policy (decreases the total supply of money and has the goal of raising interest rate to combat inflation). The independent variables were money supply (Ml), interest rate (base lending rate) and import of construction materials and mineral products, while the dependent variable was housing loan. The data have been taken from Monthly Statistical Bulletin from Bank Negara Malaysia (BNM) which consists of 6 years (from year 2000 to 2005) using monthly basis and the statistical tool that has been use was Multiple Linear Regression. From the results of the study, the housing loan (dependent variable) can be influenced by the (independent variables) which were money supply (Ml), interest rate (BLR) and also import of construction materials and mineral products. Money supply; and import of construction materials and mineral products show the positive relationship but interest rate (BLR) shows the negative relationship with the housing loan. All of these variables were significant to each other.